The coupling of alkylboronic acids and esters with Baylis–Hillman derivatives by Lewis base/photoredox dual catalysis. Issue 18 (2nd May 2019) - Ye, Hongqiang; Zhao, He; Ren, Shujian; Ye, Hongfeng; Cheng, Dongping; Li, Xiaonian; Xu, Xiaoliang
Graphical abstract: Highlights: The coupling of alkylboronic acids or esters with B-H adducts via dual catalysis. New method for the synthesis of 2-alkyl substituted acrylate derivatives. Broad scope of the substrates, moderate to excellent yields, simple operations. Abstract: Utilizing Lewis base/photoredox dual catalysis, carbon radicals generated from either alkylboronic acids or esters were coupled with Baylis–Hillman derivatives under visible light irradiation. This protocol provides a mild and operationally simple method for the synthesis of a variety of α, β-unsaturated carbonyl compounds in a broad scope of the substrates. The mechanism of Lewis base activation and reductive quenching cycle was probably involved.